Tingene sat på plads - Om afrikanernes bidrag til etableringen af byen Christiansted på St. Croix - F. Tyson, George (Slagmark - Tidsskrift for idéhistorie, 2017)
GET TING IT STRAIGHT – THE CONTRIBUTIONS OF AFRICANS TO THE ESTABLISHMENT OF THE TOWN OF CHRISTIANSTED, ST. CROIX It is the contention of this paper that Africans and Creoles of African descent were primarily responsible building much of the town of Christiansted during the Eighteenth Century. Danish/European aspirations, aesthetics and investment capital, certainly played their part, but these would have come to nothing without the skills, energy and talents of African laborers and tradesmen. The exceptional historic buildings that comprise the Christiansted Historic District stand as monuments to the outstanding Afro-Crucian craft tradition that materialized through their production. This craft tradition allowed enslaved and free Africans/Crucians to fashion their own aesthetic and it also enabled them and their families to endure and overcome enslavement and other adversities that characterized their lives under Danish rule. However there still need to be done more research that will set the historical record straight about the elaboration, human dimensions and cultural meanings of Christiansted’s and Frederiksted’s historic architecture.